A simple, low-cost device for collecting mushroom-dwelling Scaphidiinae (Coleoptera, Staphylinidae) - Von Groll, Elisa; Aloquio, Sergio; Lopes-Andrade, Cristiano (Zootaxa, 2021)
The shining fungus beetles (Coleoptera: Staphylinidae: Scaphidiinae) comprise more than 1800 described species, which are usually small (≅0.84–14.30 mm long) (Tang et al. 2014 ; Löbl & Ogawa 2016) and found on bracket and resupinate fungi, mushrooms and slime molds (Newton 1984; Löbl & Leschen 2003; Löbl 2018). They are known to be diverse in forests of tropical and subtropical regions, which contrast to the low number of species currently known from Brazil: only 34 species and two subspecies from seven genera (Löbl 2018; von Groll & Lopes-Andrade, 2021). Any active search for Scaphidiinae in the Brazilian Atlantic forest reveals a considerable abundance and diverse of these organisms (pers. obs.), but they disperse rapidly if disturbed, and the success of field collections relies on the collectors’ skills, luck and collecting techniques and devices. The most common methods and devices for collecting shinning fungus beetles are sifting leaf litter, rotten wood and fungi, flight intercept (FIT) and V-flight intercept (V-FIT) traps, aspirators, sweeping, and hand collecting (Löbl & Leschen 2003; Tang et al. 2014; Löbl et al. 2021). Hand collecting is considered the best method, because the host fungi and larvae can be collected together to make associations (Löbl & Leschen 2003).